Distributed Courts and Legitimacy: What do we Lose When we Lose the Courthouse?. (June 2018) - Rowden, Emma
While courthouses often reveal a profound gap between the professed ideals of justice and their delivery, their designs supposedly symbolize the authority of the community over the individual and lend legitimacy to the discipline occurring within. This article considers what happens to the experience and legitimacy of justice when legal participants no longer enter the courthouse, but appear remotely by videolink. Drawing on empirical evidence regarding the use of videolinks in Australian courts, this article reveals current iterations of distributed courts ignore the important symbolic function of the courthouse as the home of justice and the presence of law.